(untitled) (Studia Prawnicze / The Legal Studies, 1981)
In the life of the USSR as well as in the life of other socialist countries, the role of the organs of state administration which have a great political influence grows constantly. Embodiment of democratic principles in organization and activity of state administration is - to a significant extent - a condition for realization of the government by the people. Democratic character of state administration is reflected in its subjecting to the control of the representation; duty to make reports to these organs; taking care of the interests of various strata of population; democratic attitude towards the problems of state life. Superiority of the representation is also reflected in its right to set up basic organs of state administration. Members of executive committees are thus elected by territorial councils from among the deputees. The councils decide also about setting up the departments, boards of executive committees and about appointing their chiefs. Democratic character of the apparaturs of administration is also reflected in the principle of collectivity and in collective management. These organs are subjected to the control of the representation which had set them up and before which they. make reports. Besides this sort of permanent responsibility before the councils, administration is also subjected to the control of all the population which - among other things - means constant rise of openness of functioning of administration. This control is exercised first of all by social organizations such as trade unions, Komsomol, etc. Local councils appoint organs of people’s control as well. In order to guarantee effective and democratic operating of the apparatus of state administration, socio-political, organizational and technical aspects of this problem must be considered. Amelioration of methods of functioning of administration which occured in result of scientific and technical revolution can- not cover the first aspect, as it sometimes happens especially in the sphere of economic management where the tendency to “engineer-economic” attitude to the problems can be observed. New constitution of the USSR which considers further deepening of demo- cracy the main direction of development of socio-political system (state apparatus included) is a lasting foundation of proper attitude in solving the problems of state administration. State administration, as socio-political activity, should fully take into con- sideration the existence of objective rules of social development, the needs and interests of the people. It should work out and realize the policy which would influence these regularities and solve all the problems resulting from them.